Obliged to Help : Adolphine Fletcher Terry and the Progressive South - Bayless, Stephanie, 1983- (Book collections on Project MUSE., 2011)
Stephanie Bayless holds a master's degree in public history from the University of Arkansas at Little Rock. She is a certified archivist and currently works in the Manuscripts Division of the Butler Center for Arkansas Studies. Bayless lives in Little Rock, Arkansas, with her husband, daughter, and son.